Термодинамическое тестирование сверхкритических циклов холодильных машин и тепловых насосов - Шерстюк, А. В.; Харлампиди, Д. Х.; Братута, Эдуард Георгиевич (НТУ "ХПИ", 2011)
The analysis of regime paramaters influence on energy and exergy efficiency of refrigerating mashines and heat pumps that works by overcritical cycle with R744 as refrigerating medium has bee carried out. The methos of thermodynamic analysis of overcritical cycles has been worked out. The influence of saturation pressure for overcritical cycle on exergy losses distribution in refrigerating mashines and heat pumps has been studied out.
Keywords: холодильные машины; тепловые насосы; критическая температура; хладагент